2021
DOI: 10.32598/sija.16.1.658.2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Findings and Risk Factors of COVID-19 Infection and Death in Elderly patients Admitted to Medical Centers of Mazandaran University of Medical Sciences During 1 Year

Abstract: Objectives: The elderly are at higher risks for developing Coronavirus Disease 2019 (COVID-19). Besides, when generating the illness, they have a higher risk of death. Recognizing clinical characteristics and risk factors associated with morbidity and mortality in the elderly is necessary to prevent mortality in similar infectious diseases. Methods & Materials: This descriptive research explored the data of all geriatrics admitted following COVID-19 in the medical centers affiliated with Mazandaran Univers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Several studies in Iran emphasize that age and sex are associated with severity and death in patients with COVID-19. These studies showed that male gender, older age and existence of at least one comorbidity, especially CVD were significantly associated with the mortality rate among COVID-19 patients ( 32 34 ). These researchers suggested that preventive programs to support the elderly and special attention to male elderly cases with underlying disease are essential.…”
Section: Discussionmentioning
confidence: 97%
“…Several studies in Iran emphasize that age and sex are associated with severity and death in patients with COVID-19. These studies showed that male gender, older age and existence of at least one comorbidity, especially CVD were significantly associated with the mortality rate among COVID-19 patients ( 32 34 ). These researchers suggested that preventive programs to support the elderly and special attention to male elderly cases with underlying disease are essential.…”
Section: Discussionmentioning
confidence: 97%